Dielectric, ferroelectric and piezoelectric properties of (Ba0.7Ca0.3)Ti1-xCuxO3-xceramics - Panupong Jaiban (2018)
© 2018 Elsevier B.V. (Ba0.7Ca0.3)Ti1-xCuxO3-xceramics (where x = 0, 0.01, 0.02 and 0.03) were prepared employing a conventional solid state sintering technique. X-ray diffraction patterns and Ti K-edge X-ray Absorption Near-Edge Structure (XANES) spectra indicated a structural distortion of Cu-doped ceramics. Depending on Cu content, the features of normal ferroelectric and diffuse dielectric phase transition could be induced by the Cu addition. The temperature where maximum dielectric existed was decreased upon increase of Cu concentration. The creation of oxygen vacancies and defect dipoles caused double-like P-E loop in host material. The decrease of d33, g33and kpvalues was observed in correlation with decrease of Prin doped ceramics. The results here suggested that the electrical properties of this ceramic system may be largely tunable by Cu dopant and could be an attractive material for high-dielectric response devices.